Acquiring the Diagnosis of an Acquired Tracheoesophageal Fistula with EtCO2: A Case Discussion with Review of the Literature. (20th March 2023) - Borja, Janine Beatrice; Patel, Ghanshyam; Baloch, Luqman; Aqeel, Ammar; Chand, Mool; Korsapati, Hariprasad; Dawood, Altaf; Khan, Naser
Abstract : Acquired tracheoesophageal fistula (TEF) is a rare complication of esophageal or lung cancer. A 57-year-old male presented with complaints of vomiting, cough, 20 lb weight loss, and progressive dysphagia. Early laryngoscopy and CT chest showed a normal pharynx with an irregular thickness of the thoracic esophagus. The upper gastrointestinal endoscopy (UGIE) and upper endoscopic ultrasound (EUS) revealed a hypoechoic mass evolving as complete obstruction. During the procedure, minimal CO2 was used for insufflation; however, when attempts were made to traverse the obstruction, capnography revealed an end-tidal CO2 (EtCO2 ) estimating 90 mmHg indicating possible TEF. This case depicts the use of capnography during UGIE in diagnosing an acquired TEF.